2019
DOI: 10.1186/s12978-019-0734-5
|View full text |Cite
|
Sign up to set email alerts
|

Parenting perspective on the psychosocial correlates of adolescent sexual and reproductive health behavior among high school adolescents in Ethiopia

Abstract: Background While parents are a crucial part of the social environment in which adolescents live, learn and earn, they could play important roles in efforts to prevent adolescent sexual and reproductive health (SRH) risk behaviors and promote healthy development. Involving parents in prevention programs to risky SRH practices in adolescents requires understanding of the effect of different parenting practices and styles on these behaviors. The purpose of this study was to investigate the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
4
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 33 publications
3
15
4
5
Order By: Relevance
“…Emerging data also showed that when parents maintain strict and authoritative parenting style that does not include comprehensive sex education, adolescents tend to engage in risky sexual acts in the university. This disagrees with the findings of Yimer and Ashebir [ 29 ], which reported that authoritative parenting, is associated with decreased odds of engaging in risky sexual behaviour. In this study, participants from authoritative homes see the university environment as a place to do what they were prevented from doing at home, which includes exploring their sexuality.…”
Section: Discussioncontrasting
confidence: 99%
“…Emerging data also showed that when parents maintain strict and authoritative parenting style that does not include comprehensive sex education, adolescents tend to engage in risky sexual acts in the university. This disagrees with the findings of Yimer and Ashebir [ 29 ], which reported that authoritative parenting, is associated with decreased odds of engaging in risky sexual behaviour. In this study, participants from authoritative homes see the university environment as a place to do what they were prevented from doing at home, which includes exploring their sexuality.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the study of Nair (2012) and Yimer (2019) found that the factors that influence parenting communication related to sexuality matters are knowledge. Lack of knowledge and uncertainty about what they are going to teach to children is a reason behind parents who do not discuss about sexual and reproductive health.…”
Section: Factors Influencing Communication Of Sexual and Reproductive Healthmentioning
confidence: 99%
“…This finding is in line with other studies in Ethiopia reporting that youths who had parent-adolescent communication were less likely to commence sexual activity or have multiple sexual partners than their counterparts. [35][36][37] Similarly, studies conducted on the role of parents on adolescent SRH behavior in sub-Saharan Africa have also indicated that good family communication has been associated with less engagement in risky sexual behavior. Adolescents who engaged in conversations about sexrelated topics with their parents were less likely to report being sexually experienced, reported fewer lifetime sex partners, and were more likely to report using condoms.…”
Section: Discussionmentioning
confidence: 99%
“…Those who had had sexual intercourse were again asked about age at first sexual intercourse, number of sexual partners, and condom utilization. Respondents who had at least one of behavior among sexual debut before age 15 years, inconsistentcondom use (or not using condoms at all) in the last 6 months, and multiple sexual partners were classified as engaging in risky sexual behavior 36 and were "1". The remaining (ever abstained, secondary abstinence or consistent condom use for the last 6 months) were classified as engaging in safe sexual behavior and coded "0".…”
Section: Variables and Measurementmentioning
confidence: 99%
See 1 more Smart Citation